Prognostic Significance of Early Postoperative Choroidal Detachment in Patients with Congenital Glaucoma Operated with Nonpenetrating Deep Sclerectomy - Shaikha H. Aldossari; Konrad Schargel; Ibrahim Aljadaan; Khabir Ahmad; Rakan Gorinees; Nouf Alzendi; Gorka Sesma (Journal of Ophthalmology)
Objective. To assess the association between early postoperative choroidal detachment and intraocular pressure (IOP) following nonpenetrating deep sclerectomy in pediatric primary congenital glaucoma. Design. Retrospective double-arm cohort study. Setting. Single center in Saudi Arabia. Patients. Seventy-two eyes of 45 patients were evaluated. Primary congenital glaucoma patients aged 0–3 years undergoing nonpenetrating deep sclerectomy as the first procedure from 2014 to 2021 were divided into groups with (n = 20) and without (n = 52) postoperative choroidal detachment. Main Outcome Measures. The primary outcome was complete surgical success, defined as an intraocular pressure below 21 mmHg without medication or additional surgery at 24 months. The intraocular pressure was evaluated in the first 72 hours after surgery and at 1, 3, 6, 12, 18, and 24 months. Kaplan–Meier survival analysis over 24 months was used to evaluate this outcome in both cohorts. The secondary outcome was the time to choroidal detachment resolution. Results. There was no significant difference in surgical success between choroidal detachment and nonchoroidal detachment groups (P=0.12). Preoperative and 2-year postoperative intraocular pressure was similar between groups, with a significant decrease in intraocular pressure from baseline (P<0.001) in both the groups. The median time to choroidal detachment resolution was 27 days, and 90% of choroidal detachment cases were resolved with medical therapy. Conclusions. Postoperative choroidal detachment does not appear to significantly impact intraocular pressure or surgical success at 24 months following nonpenetrating deep sclerectomy for primary congenital glaucoma. Choroidal detachment typically resolves within one month of treatment. These findings suggest that transient choroidal detachment has a benign course in patients with primary congenital glaucoma undergoing deep sclerectomies.